DESCRIBING PICTURE STRATEGY TO TEACH SPEAKING SKILLS TO THE SEVENTH-GRADE STUDENTS OF MADRASAH TSANAWIYAH QUR'ANIAH MATARAM - Arini, Arini; ardayati; Oktaviani, ayu (Lingustic, Literature and English Education, 2023)
The aim of the study was to find out whether or not it is significantly effective to teach speaking by using describing picture strategy to the seventh-grade students of Madrasah Tsanawiyah Qur’aniah Mataram. The researcher used a Pre-Experimental design. The researcher used a performance test in the form of an oral test. The data were collected by using Brown's theory. The findings of this study are that significantly effective in teaching speaking by using the describing picture strategy to the seventh-grade students of Madrasah Tsanawiyah Qur'aniah Mataram.